Escarificação e gessagem na descompactação do solo sob sistema plantio direto - Barros, Leonardo Rodrigues (2017)
In areas under no-tillage system in Brazil’s Cerrado, compaction is becoming increasingly frequent. It is noticeable because there are changes in soil physical properties and in the root system as well as reduction in crop yields. The practices of scarification and gypsum application are alternatives to mitigate compaction. In this sense, the objective of this work was to evaluate the effects and length of scarification and gypsum application on soil physical and chemical properties and on soybean yield under a no-tillage system deployed 15 years ago. The study was divided into two steps. The first step consisted of the diagnosis of soil compaction in an area of 315 ha divided into a 63-point sampling grid, where each point represented five hectares in Joviânia, GO. In this area, moisture samples were collected and a penetrometer was used at each point of the mesh, in the 0.0-0.20 m and 0.20-0.40 m layers, in three periods: 1) prior to the scarification; 2) at 60 days after soil scarification; and 3) at 390 days after scarification. Based on the results found in the first step, one of the points of this area was selected to perform the second step of the work, which consisted in setting up 24 plots, divided into six randomized blocks, composed of four treatments: (C) = Control, (S) = Scarification, (G) = Gypsum application, (G+S) = Gypsum application and scarification. The following properties were determined: soil fertility (MOS, pH, H+Al, P, K, Ca and Mg), gravimetric moisture and physical indicators in four soil layers, in addition to soybean yield. The data were submitted to analysis of variance and when they were significant, Dunnet’s test was applied for comparison of treatments at the level of probability of 5% of error (p<0.05). These results show that scarification offered short-lasting benefits, because although there was a reduction in resistance to penetration at 60 days after scarification, these values already showed a significant increase in resistance to penetration at 390 days after scarification. Scarification affected macroporosity and total porosity positively in the 0-0,10 m layer. Macroporosity is a physical indicator of great influence in determining soybean yield under a no-tillage system. The use of agricultural gypsum resulted in increased root volume and deeper root systems.